Management of dentine hypersensitivity: efficacy of professionally and self‐administered agents. (April 2015) - West, Nicola X.; Seong, Joon; Davies, Maria
Abstract: Context: The gold standard treatment modality for dentine hypersensitivity has not yet been established. This review examines the effectiveness of self and professionally applied treatments for the reduction in pain from dentine hypersensitivity. Materials and Methods: Electronic (three databases) and hand searches were performed 14–21 July 2014 to identify randomized controlled trials for the treatment of dentine hypersensitivity. Results: This systematic review provided numerous treatment modalities for dentine hypersensitivity. Eleven agents and 105 Randomized Controlled Trials were robust enough to be included. The studies varied considerably in design, observation period, active agents, formulation of the whole agent, negative and positive controls and comparator products investigated. The stimuli used were predominantly airblast and tactile or thermal. Due to the heterogeneity between the studies and lack of direct comparison between agents there was insufficient data to undertake a meta‐analysis to compare agents for meaningful conclusions. Best available evidence for each treatment agent has been documented as a narrative. Conclusions: Treatments including stannous fluoride, arginine, calcium sodium phosphosilicate and strontium toothpaste appear to be clinically effective for the treatment of dentine hypersensitivity compared to comparators and controls. There is limited evidence to confirm the relative effectiveness of individual professionally applied agents.